If virtual gynecology clinics are here to stay, we need to include everyone - Elizabeth Ball, PhD, MD; Carol Rivas, PhD; Rehan Khan, MRCOG (Elsevier, 2022)
Before the COVID-19 pandemic virtual clinics in gynecology were not commonplace in the United Kingdom or most other countries. Owing to the need to reconfigure health provision to caring for COVID-19 patients, reducing footfall in hospitals and restricted movement, telemedicine was rapidly introduced at scale in hospitals thought the United Kingdom. This happened without much consultation with service users and healthcare professionals. It is anticipated that after the pandemic, telemedicine will remain to some extent. The authors report how their hospital how their place of work, a large London teaching hospital, adopted virtual phone consultations in gynecology, along with a countrywide survey of 200 service users and healthcare professionals. Now it is important carry out a robust evaluation of outcomes (both clinician and patient experience) and also to take care that service users from disadvantaged backgrounds do not lose out.